2022
DOI: 10.54371/jiip.v5i11.1071
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kegiatan Kampus Mengajar Angkatan 2 terhadap Peningkatan Literasi Numerasi Siswa di Sekolah Dasar Akreditasi C

Abstract: Sejak kasus pertama virus corona diumumkan oleh Presiden Joko Widodo pada awal maret 2020, Indonesia menghadapi kesulitan hampir disetiap bidang kehidupan, Pada bidang pendidikan sendiri juga sangat merasakan dampak dari pandemi covid, yaitu menyebabkan sekolah-sekolah harus mau atau tidak mau menerapkan pembelajaran secara online untuk mengurangi penyebaran covid. Namun berdasarkan implementasi BDR, ternyata tidak sesuai dengan yang diharapkan. Keberadaan dan pemberlakuan pembelajaran online justru menyebabka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Research on campus teaching programs in remote schools is actually not new because the target schools of this program are schools with 3T criteria (underdeveloped, outermost, foremost) and schools with C accreditation. Similar research has been conducted by Andrian Tanzani in remote schools at SDN 013 Nunukan, with the finding that the teaching campus, especially Batch 2, contributed to increasing student numeracy literacy during the Covid 19 pandemic in the 3T area (Thanzani, 2022), similar to the results of Surya Pardede's research at SDN 15 Bengkayang which is also a 3T area, that the campus program teaches for approximately 5 months to help students' numeracy literacy which had decreased at the beginning of the covid 19 pandemic (Pardede, Ongsina, et al, 2022). Meanwhile, in the research results of AR Fahmi et al, found that in remote schools at SDN 48 Bengkulu Tengah, where learning activities could not be carried out online due to limited school facilities and infrastructure as well as complaints from student parents who could not provide gadgets to support online learning activities, the team the teaching campus at the school helps the teacher assembly carry out teaching and learning activities face-to-face, plus innovating learning media and adapting technology by implementing health protocols so students can study comfortably (Fahmi et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
“…Research on campus teaching programs in remote schools is actually not new because the target schools of this program are schools with 3T criteria (underdeveloped, outermost, foremost) and schools with C accreditation. Similar research has been conducted by Andrian Tanzani in remote schools at SDN 013 Nunukan, with the finding that the teaching campus, especially Batch 2, contributed to increasing student numeracy literacy during the Covid 19 pandemic in the 3T area (Thanzani, 2022), similar to the results of Surya Pardede's research at SDN 15 Bengkayang which is also a 3T area, that the campus program teaches for approximately 5 months to help students' numeracy literacy which had decreased at the beginning of the covid 19 pandemic (Pardede, Ongsina, et al, 2022). Meanwhile, in the research results of AR Fahmi et al, found that in remote schools at SDN 48 Bengkulu Tengah, where learning activities could not be carried out online due to limited school facilities and infrastructure as well as complaints from student parents who could not provide gadgets to support online learning activities, the team the teaching campus at the school helps the teacher assembly carry out teaching and learning activities face-to-face, plus innovating learning media and adapting technology by implementing health protocols so students can study comfortably (Fahmi et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
“…d) memberi manfaat bagi mahasiswa untuk mengasah jiwa kepemimpinan, soft skills, karakter dalam berinovasi dan berkolaborasi. e) memberikan inspirasi dan motivasi belajar bagi para peserta didik untuk dijadikan acuan meraih masa depan (S. D. Pardede et al, 2022). Peran mahasiswa kampus mengajar untuk membantu sekolah dalam proses pembelajaran melalui penguatan literasi, numerasi dan membantu kegiatan di sekolah (Kurniasari et al, 2023).…”
Section: Pendahuluanunclassified
“…Previous research with the title "Analisis Kegiatan Kampus Mengajar Angkatan 2 terhadap Peningkatan Literasi Numerasi Siswa di Sekolah Dasar Akreditasi C" by (Pardede et al, 2022a) is more focused on analyzing students' abilities, Based on the results of the research that has been carried out, it can be concluded that the Kampus Mengajar program can help improve student learning ability literacy. Increased Student Numeracy Literacy by student numeracy which had previously dropped.…”
Section: A Introductionmentioning
confidence: 99%